Sequential change in olfaction and (non) motor symptoms: the difference between anosmia and non-anosmia in Parkinson’s disease - Fang, Ting-Chun; Tsai, Yu-Shan; Chang, Ming-Hong (Frontiers in Aging Neuroscience, 2023)
Introduction Hyposmia is a common prodrome in patients with Parkinson’s disease (PD). This study investigates whether olfactory changes in PD differ according to the degree of olfactory dysfunction and whether there are changes in motor and non-motor symptoms. Methods The 129 subjects with PD were divided into two groups: anosmia and non-anosmia. All cases were reassessed within 1–3 years after the initial assessment. The assessment included the MDS-Unified PD Rating Scale (MDS-UPDRS), the University of Pennsylvania Smell Identification Test (UPSIT), Beck’s Depression Inventory-II (BDI-II), Montreal Cognitive Assessment (MoCA), and equivalence dose of daily levodopa (LEDD). The generalized estimating equation (GEE) model with an exchangeable correlation structure was used to analyze the change in baseline and follow-up tracking and the disparity in change between these two groups. Results The anosmia group was older and had a longer disease duration than the non-anosmia group. There was a significant decrease in UPSIT after follow-up in the non-anosmia group (β = −3.62, p < 0.001) and a significant difference in the change between the two groups (group-by-time effect, β = 4.03, p < 0.001). In the third part of the UPDRS motor scores, there was a tendency to increase the score in the non-anosmia group compared to the anosmia group (group-by-time effect, β = −4.2, p < 0.038). There was no significant difference in the group-by-time effect for UPDRS total score, LEDD, BDI-II, and MoCA scores. Discussion In conclusion, this study found that olfactory sensation may still regress in PD with a shorter disease course without anosmia, but it remains stable in the anosmia group. Such a decline in olfaction may not be related to cognitive status but may be associated with motor progression.